Evaluation of cumulative impacts of stormwater detention ponds on watershed in tropical region - Chai, Pin Kang (2014)
Application of source-control approach for catchment wide implementation is increasing in watershed stormwater management, especially stormwater detention pond. The study of cumulative impact of stormwater detention ponds in watershed scale have found out the pre-development peak flow rate can’t be maintained. However, there is no related study found on tropical watershed. It is important to know whether the hydrologic response is still same in different climate region as different climatic factor influences the performance of detention pond. The research is intended to evaluate the cumulative impact of stormwater detention ponds in watershed scale under tropical climate. The study was carried out in selected upstream section of Skudai river catchment. HEC-HMS software with extension of HEC-GeoHMS was applied to develop hydrologic model for assessing research objective. Analyses of hydrographs for post-development with detention ponds and post-development without detention pond scenarios were performed for single storm event, synthetic storms and time-series discharge. The overall performance of stormwater detention ponds and catchment outlet are evaluated to examine cumulative impact with design storm of ARI of 2-, 5-, 10- and 20-year. The overall peak discharge reduction indicated by each detention pond vary from 13.9 to 76.6%, 6.8 to 78,5%, 4.1 to 80% and 2.7 to 81.3% over ARIs, respectively. The overall performance of catchment outlet over ARIs are 32.6%, 28.8%, 28.8% and 28.6% respectively. About 30% efficiency loss recorded at catchment outlet over ARIs is the evidence of cumulative impact of stormwater detention ponds on a catchment scale in tropical climate